Exchange rate undervaluation, economic institutions and exports performance: evidence from firm-level data. (19th February 2021) - Elbadawi, Ibrahim; Zaki, Chahir
Exploiting a unique firm level dataset available for four countries (Egypt, Jordan, Kuwait and Yemen), this paper assesses the role of real exchange rate (RER) undervaluation as a determinant of the quantity of exports (intensive margin) as well as the probability of exporting more products or opening new export destinations (extensive margin) We find that moderate RER up to a certain threshold unconditionally promotes firms' exports at the intensive margin, for all firm sizes and for financially developed or underdeveloped economies alike At the market and product-extensive margins, however, the evidence suggests that the undervaluation export promotion effect is conditional on the size of the firm and confined to medium and large firms only Moreover, RER undervaluation becomes a counter-productive policy instrument for promoting exports at the product-extensive margin in financially developed economies, though it continues to be a viable export strategy for promoting exports at the market-extensive margin.